Pengaruh Pengelolaan Kelas Terhadap Motivasi Belajar Peserta Didik Kelas IX MTS YMPI Rappang Kabupaten Sidrap - Usman Noer; Nuryani Nuryani (Al-Ishlah: Jurnal Pendidikan Islam, 2018)
ABSTRACTClass management is needed by the teacher in utilizing the potential of the class,making learning and learning to remain optimal, enjoyable and to improve optimalconditions in the event of a disruption in the learning process. Motivation to learnis an impulse from inside and outside the self of students who can move it to bemore active in learning activities in order to obtain the desired goals by changingbehavior both from the aspects of thought, affective and psychomotor. This studydiscusses the motivation of the class towards the motivation to learn history andthe Islamic participants of class IX of YMPI Rappang's MTs. This type of researchis field research with associative quantitative design. As a technique of datacollection, namely observation, questionnaire and documentation with descriptiveand infrequent analysis techniques. The results showed that: (1) Management ofclasses in class IX of YMPI Rappang MTs showed a good category with apercentage rate of 77.4%. (2) Learning motivation of students shows a goodcategory with a percentage of 85.4%. (3) There is a significant difference betweenthe learning class towards the learning motivation of YMPI Rappang's IX gradestudents. This can be seen from the results of manual calculations tcount = 9.406>t table = 1998 and the value of R Square or r2 obtained 0.564. The value of XI forstudents 'learning motivation in Islamic culture class (Y) was 56.4%, while 43.6%of students' learning motivation at MTs YMPI Rappang was related to othervariables not expected by researchers.